External Esophageal Stenting Technique in Palliation for Tracheal Agenesis in a Case of Esophageal Lung: A Lesson Learned from the Experience for Tracheomalacia - Taichi Hirotani; Ryo Tamura; Makoto Ando; Hideaki Okajima (MDPI AG, 2023)
Tracheal agenesis (TA) is a rare congenital anomaly with an incidence of 1 per 50,000 newborns. It appears at birth with severe respiratory distress, cyanosis, and inaudible crying. Prompt esophageal intubation and long-term management of the esophageal airway are essential to overcome this catastrophic condition. In the long-term management, external stenting of the esophageal airway has been reported as promising to support the fragile esophageal wall; this technique was taken from the surgery for tracheomalacia. We experienced a case of an infant with tracheal agenesis whose respiratory status was stabilized after external esophageal stenting. The stenting was performed based on a lesson learned in the extensive experience in the surgical treatment for tracheomalacia, and the surgical techniques for successful stenting are herein described.